PENGARUH CITRA MEREK, WORD OF MOUTH DAN IKLAN TERHADAP KEPUTUSAN PERPINDAHAN MEREK - Grace Radamuri; Naili Farida; Reni Shinta Dewi (Universitas Diponegoro, 2013)
This research purpose to find out influence of brand image, word of mouth, and advertising on brand switching decisions of non-BlackBerry mobile phone to the BlackBerry. This research included in explanatory. Taked 94 respondents as sample with purposive sampling method. Collecting data used questionnaire. Hypotheses tested by correlation coefficient, simple linear regression, multiple linear regression, t test, F test, and determination coefficient. The result of this research show that brand image dimension have significant influence to brand switching decisions,word of mouth dimension have significant influence to brand switching decisions, adevertising dimension have significant influence to brand switching decision. Brand image, word of mouth and advertising dimension in partial and simultaneous have significant influence to brand switching decisions.